2015
DOI: 10.1371/journal.pone.0145543
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of HIV and Safe Male Circumcision in High HIV Prevalence Fishing Communities on Lake Victoria, Uganda

Abstract: BackgroundIn 2010, the Uganda Ministry of Health introduced its Safe Male Circumcision (SMC) strategy for HIV prevention with the goal of providing 4.2 million voluntary medical male circumcisions by 2015. Fishing communities, where HIV prevalence is approximately 3–5 times higher than the national average, have been identified as a key population needing targeted HIV prevention services by the National HIV Prevention Strategy. This study aimed to understand perceptions of HIV and identify potential barriers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…This should be a consideration for programme implementers because beliefs of this kind could put some newly circumcised men that adhere to them, as well as their sexual partners at the risk of HIV infection. This belief has also been reported among fishing communities on lake Victoria, Uganda [14,22] and in unpublished work in eastern Uganda [23]. It is also loosely mentioned in a national supervision report for HIV/AIDs activities [24], which may indicate that it is not only limited to this study.…”
Section: Discussionsupporting
confidence: 73%
“…This should be a consideration for programme implementers because beliefs of this kind could put some newly circumcised men that adhere to them, as well as their sexual partners at the risk of HIV infection. This belief has also been reported among fishing communities on lake Victoria, Uganda [14,22] and in unpublished work in eastern Uganda [23]. It is also loosely mentioned in a national supervision report for HIV/AIDs activities [24], which may indicate that it is not only limited to this study.…”
Section: Discussionsupporting
confidence: 73%
“…Concerns about misunderstanding the level of protection from circumcision have also been reported in southern Africa [52, 53] and among fishing communities in Uganda [27]. Such misconceptions could be due to information from less reliable sources within communities and/or misunderstandings of SMC social marketing messages, as indeed feared by some men in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Other reasons reported such as better penile hygiene, risk reduction to some STIs and cervical cancer prevention to partners, are also portrayed in SMC messages to the public in Uganda [45, 46]. Studies conducted in other sub Saharan countries [47, 48, 27, 29, 26] have also reported that these reasons play a role in influencing men to circumcise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some observational studies conducted in the field of VMMC have found that men who are circumcised are more likely to engage in risky sexual behaviour than those who are uncircumcised. 15,17,20 In Africa there is a strong belief that circumcision improves sexual performance, especially among adults, and there is also a concern that this can increase the risk of HIV transmission. Equally so, there is a strong believe that the perceptions that communities hold about VMMC can likely affect their sexual behaviours after undergoing the procedure.…”
Section: Introductionmentioning
confidence: 99%